Respuesta :

Hey there!

[tex]\mathsf{(6.51\times10^4) - (3.26\times10^4)}[/tex]

[tex]\mathsf{= 6.51\times 10^4 - 3.26\times10^4}[/tex]

[tex]\mathsf{10^4}\\\mathsf{= 10 \times10\times10\times10}\\\mathsf{= 100\times 100}\\\mathsf{= \bf 10,000}[/tex]

[tex]\mathsf{= 6.51 \times 10,000 - 3.26 \times 10,000}[/tex]

[tex]\mathsf{6.51 \times 10,000}\\\mathsf{= \bf 65,100}[/tex]

[tex]\mathsf{65,100 - 3.26 \times10,000}[/tex]

[tex]\mathsf{3.26 \times 10,000}\\\mathsf{= \bf 32,600}[/tex]

[tex]\mathsf{= 65,100 - 32,600}[/tex]

[tex]\mathsf{= \bf 32,500}[/tex]

[tex]\boxed{\boxed{\huge\textsf{Answer: \bf 32,500}}}\huge\checkmark[/tex]

[tex]\large\textsf{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]

Answer:

[tex]{ \tt{6.51 \times {10}^{4} - 3.26 \times {10}^{4} }} \\ = { \tt{(6.51 - 3.26) \times {10}^{4} }} \\ = { \tt{3.25 \times {10}^{4} }}[/tex]